Tradição e ruptura: Pierre Boulez e a formação do cânone no pós-guerra (1946-1954) - Rizek, João Gabriel [UNESP] (2014)
The concepts of Canon and Tradition are of the most importance inside the artistic debate. Not only they shape our understanding of what music should be but also what we take as being classical music. Their mechanisms help us shape practices and transform what we take as being theories. Through the investigation of the canon’s mechanisms, as exemplified by several notions ranging from musicology, philosophy and literary criticism, we will investigate in this dissertation how one particular canon took shape. It has to do with the music being created and played in the Post-war period, that is, serialism. Far from being the only music composed in those years, Pierre Boulez, among several musical institutions and publications, took every measure to guarantee its power among all the other artistic languages. We will analyze here how Boulez defended that music, being responsible for the dimension it has achieved in those years. In order to do that we will investigate more accurately Boulez’s essays collected in Stocktakings from an Apprenticeship. As we will see, far from being an arbitrary solution, the manipulation of the canon has political implications, responsible for what governs our ways of understanding and practicing music.